Analysis of Work Ability, Compensation, And Supervision of Employee Performance at PT Capella Multidana Medan, Nibung Street Branch - Halimatussa'diah (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
This study aims to determine the effects of work capability, compensation, and supervision on the performance of employees at PT Capella Multidana Medan, Jalan Nibung Branch. The population in this research includes all employees at this branch, totaling 61 individuals, who also comprised the sample. The sampling technique used was simple random sampling, and the study was conducted in 2023, with data collected via questionnaires. This research adopts an associative-quantitative approach and processes data using SPSS version 24. The results indicate that work capability, compensation, and supervision positively and significantly influence employee performance at PT Capella Multidana Medan, Jalan Nibung Branch, both partially and simultaneously. The t-test (partial) analysis shows that work capability has a regression value of 0.486 with a t-value of 5.705 and a significance of 0.000. Compensation has a regression value of 0.279 with a t-value of 3.967 and a significance of 0.000, while supervision has a regression value of 0.100 with a t-value of 2.147 and a significance of 0.036. The F-test (simultaneous) produced an F-value of 186.270 with a significance of 0.000, indicating that work capability, compensation, and supervision all significantly impact employee performance. The most dominant factor was work capability, which explained 90.7% of performance, with the remaining 9.3% attributed to other factors